Generation of the CSSi020-A (14437) iPSC line from a patient carrying a copy number variation (CNV) in the 17p11.2 chromosome region - Angela Maria Giada Giovenale; Elisa Maria Turco; Martina Mazzoni; Ilaria Ferrone; Barbara Torres; Laura Bernardini; Edvige Vulcano; Daniela Ferrari; Roberta Onesimo; Stefano D’Arrigo; Giuseppe Zampino; Maria Pennuto; et al. (Stem Cell Research)
Smith-Magenis syndrome (SMS) is a complex neurodevelopmental disorder with a birth incidence of 1:25,000. SMS is caused by haploinsufficiency of the retinoic acid-induced retinoic acid1 (RAI1) gene, determined by an interstitial deletion of ∼ 3.7 Mb (17p11.2, including the RAI1 gene) in 90 % of cases and a mutation on the RAI1 gene in only 10 % of cases. We generated and characterized a human pluripotent stem cell line (hIPSCs) derived from primary fibroblasts of a 17-year-old woman carrying a 17p11.2 deletion including the RAI1 gene.